Exposure to loud noise and risk of vestibular schwannoma: results from the INTERPHONE international case‒control study - Isabelle Deltour; Brigitte Schlehofer; Amélie Massardier-Pilonchéry; Klaus Schlaefer; Bruce Armstrong; Graham G Giles; Jack Siemiatycki; Marie-Elise Parent; Daniel Krewski; Mary McBride; Christoffer Johansen; Anssi Auvinen; et al. (Scandinavian Journal of Work, Environment & Health, 2019)

(untitled)
OBJECTIVE: Studies of loud noise exposure and vestibular schwannomas (VS) have shown conflicting results. The population-based INTERPHONE case‒control study was conducted in 13 countries during 2000–2004. In this paper, we report the results of analyses on the association between VS and self-reported loud noise exposure. METHODS: Self-reported noise exposure was analyzed in 1024 VS cases and 1984 matched controls. Life-long noise exposure was estimated through detailed questions. Odds ratios (OR) and 95% confidence intervals (CI) were estimated using adjusted conditional logistic regression for matched sets. RESULTS: The OR for total work and leisure noise exposure was 1.6 (95% CI 1.4–1.9). OR were 1.5 (95% CI 1.3–1.9) for only occupational noise, 1.9 (95% CI 1.4–2.6) for only leisure noise and 1.7 (95% CI 1.2–2.2) for exposure in both contexts. OR increased slightly with increasing lag-time. For occupational exposures, duration, time since exposure start and a metric combining lifetime duration and weekly exposure showed significant trends of increasing risk with increasing exposure. OR did not differ markedly by source or other characteristics of noise. CONCLUSION: The consistent associations seen are likely to reflect either recall bias or a causal association, or potentially indicate a mixture of both.